If a, ß are the roots of x² + P(x+1)+c = 0 then (1+a) (1+B) =
Answers
Answered by
3
Answer:
Step-by-step explanation:
for this question, we must know that for any polynomial
and the zeroes are a, ß, then
a + ß = -b/a ---------1
aß = c/a ------------2
now for the question \
x² + P(x+1)+c = 0
x²+Px+P+c = 0
therefore we get a = 1, b=P, c=(P+c) -------------3
therefore,
for (1+a)(1+ß)= answer
1 + a + ß + aß = answer
using equation 1, 2 and 3
1 + (-P/1) + ((P+c)/1)
1 - P + P + c
1+c = answer
HOPE THIS HELPS
CHEERS MATE, PLEASE MARK BRAINLIEST
Answered by
3
Answer:
hope you UNDERSTOOD this answer
Attachments:
![](https://hi-static.z-dn.net/files/d78/b1e7f73e0c47b8e314ceec3a4ad12f96.jpg)
Similar questions